The role of industrial nitrogen in the global nitrogen biogeochemical cycle - Gu, Baojing (Nature Publishing Group, 2013)
Haber-Bosch nitrogen (N) has been increasingly used in industrial products, e.g., nylon, besides fertilizer. Massive numbers of species of industrial reactive N (Nr) have emerged and produced definite consequences but receive little notice. Based on a comprehensive inventory, we show that (1) the industrial N flux has increased globally from 2.5 to 25.4 Tg N yr(−1) from 1960 through 2008, comparable to the NO(x) emissions from fossil fuel combustion; (2) more than 25% of industrial products (primarily structural forms, e.g., nylon) tend to accumulate in human settlements due to their long service lives; (3) emerging Nr species define new N-assimilation and decomposition pathways and change the way that Nr is released to the environment; and (4) the loss of these Nr species to the environment has significant negative human and ecosystem impacts. Incorporating industrial Nr into urban environmental and biogeochemical models could help to advance urban ecology and environmental sciences.